(untitled) (Academicia Globe: Inderscience Research, 2023)
Interior decoration of an apartment with wood in a modern residential building is a common option for interior design. Wood is an environmentally friendly, natural material and a durable product. Which has the properties to absorb unpleasant odors in the apartment, create comfort and warm atmosphere in a residential building. When decorating the interior of an apartment with wood in Uzbekistan, there are its own style directions in each region, which are determined by the content of national traditions, as well as its elements, social conditions associated with bygone rites and everyday life.